Stereotactic ablative radiotherapy versus standard radiotherapy in stage 1 non-small-cell lung cancer (TROG 09.02 CHISEL): a phase 3, open-label, randomised controlled trial. Issue 4 (April 2019) - Ball, David; Mai, G Tao; Vinod, Shalini; Babington, Scott; Ruben, Jeremy; Kron, Tomas; Chesson, Brent; Herschtal, Alan; Vanevski, Marijana; Rezo, Angela; Elder, Christine; Skala, Marketa; et al.
Summary: Background: Stereotactic ablative body radiotherapy (SABR) is widely used to treat inoperable stage 1 non-small-cell lung cancer (NSCLC), despite the absence of prospective evidence that this type of treatment improves local control or prolongs overall survival compared with standard radiotherapy. We aimed to compare the two treatment techniques. Methods: We did this multicentre, phase 3, randomised, controlled trial in 11 hospitals in Australia and three hospitals in New Zealand. Patients were eligible if they were aged 18 years or older, had biopsy-confirmed stage 1 (T1–T2aN0M0) NSCLC diagnosed on the basis of 18 F-fluorodeoxyglucose PET, and were medically inoperable or had refused surgery. Patients had to have an Eastern Cooperative Oncology Group performance status of 0 or 1, and the tumour had to be peripherally located. Patients were randomly assigned after stratification for T stage and operability in a 2:1 ratio to SABR (54 Gy in three 18 Gy fractions, or 48 Gy in four 12 Gy fractions if the tumour was <2 cm from the chest wall) or standard radiotherapy (66 Gy in 33 daily 2 Gy fractions or 50 Gy in 20 daily 2·5 Gy fractions, depending on institutional preference) using minimisation, so no sequence was pre-generated. Clinicians, patients, and data managers had no previous knowledge of the treatment group to which patients would be assigned; however, the treatment assignment was subsequently open label (because of the nature of the interventions). The primary endpoint was time to local treatment failure (assessed according to Response Evaluation Criteria in Solid Tumors version 1.0), with the hypothesis that SABR would result in superior local control compared with standard radiotherapy. All efficacy analyses were based on the intention-to-treat analysis. Safety analyses were done on a per-protocol basis, according to treatment that the patients actually received. The trial is registered withClinicalTrials.gov (NCT01014130 ) and the Australia and New Zealand Clinical Trials Registry (ACTRN12610000479000). The trial is closed to new participants. Findings: Between Dec 31, 2009, and June 22, 2015, 101 eligible patients were enrolled and randomly assigned to receive SABR (n=66) or standard radiotherapy (n=35). Five (7·6%) patients in the SABR group and two (6·5%) in the standard radiotherapy group did not receive treatment, and a further four in each group withdrew before study end. As of data cutoff (July 31, 2017), median follow-up for local treatment failure was 2·1 years (IQR 1·2–3·6) for patients randomly assigned to standard radiotherapy and 2·6 years (IQR 1·6–3·6) for patients assigned to SABR. 20 (20%) of 101 patients had progressed locally: nine (14%) of 66 patients in the SABR group and 11 (31%) of 35 patients in the standard radiotherapy group, and freedom from local treatment failure was improved in the SABR group compared with the standard radiotherapy group (hazard ratio 0·32, 95% CI 0·13–0·77, p=0·0077). Median time to local treatment failure was not reached in either group. In patients treated with SABR, there was one grade 4 adverse event (dyspnoea) and seven grade 3 adverse events (two cough, one hypoxia, one lung infection, one weight loss, one dyspnoea, and one fatigue) related to treatment compared with two grade 3 events (chest pain) in the standard treatment group. Interpretation: In patients with inoperable peripherally located stage 1 NSCLC, compared with standard radiotherapy, SABR resulted in superior local control of the primary disease without an increase in major toxicity. The findings of this trial suggest that SABR should be the treatment of choice for this patient group. Funding: The Radiation and Optometry Section of the Australian Government Department of Health with the assistance of Cancer Australia, and the Cancer Society of New Zealand and the Cancer Research Trust New Zealand (formerly Genesis Oncology Trust).